Testing a Popular Smartphone Application for Colour Vision Assessment in Healthy Volunteer Subjects. (4th March 2021) - Fliotsos, Michael J; Zhao, Jiawei; Pradeep, Tejus; Ighani, Mehrnaz; Eghrari, Allen O
ABSTRACT: We aimed to compare the Ishihara pseudoisochromatic colour vision test with a colour vision test from a popular smartphone application (EyeHandBook [EHB]) using digital image processing to simulate colour vision deficiencies. Three digital versions of the Ishihara and EHB slides were created: full colour; 32 bit- greyscale (removing all colour information); and blue channel (to simulate red-green colour vision deficiencies). Twenty healthy volunteers were shown each colour-edited plate. The answers they reported were compared with what would be expected for that colour-simulation scenario based on the answer key provided in the Ishihara booklet ("expected" answer). There were nine plates that had comparable patterns between the EHB and Ishihara test. We found no significant difference in the overall proportion of "expected" answers for the full colour (p = .35), 32 bit-greyscale (p = .39) and blue channel (p = .22) conditions. There were significant differences between the proportion of "expected" answers among six individual colour- edited plates (p < .05 for each). Colour vision assessment from the EHB is distinct from comparable Ishihara plates. Clinical scenarios that require serial assessment of colour vision may benefit from using the same modality consistently rather than exchanging between the two tests with the assumption of equivalence. Refinement of digital colour editing techniques beyond 32-bit greyscale and RGB channel splitting is necessary in order to accurately simulate colour vision deficiency.